Performing processes - Mock, Roberta (Intellect, 2000)
Live performance continues to be created every time it is performed. This book explores the dynamic relationship between creative process, presentation and spectator response to provide students and scholars in Drama with new insights on performance from poetry to pantomime. These essays make parallels between areas of performance that are rarely, if ever, compared. They present the basis for an overall theory of how 'conception', 'development', 'presentation' and 'reception' are fused together to make up the overall 'performance'. This study investigates the relationship between the process o.